Wpływ bezpośrednich inwestycji zagranicznych na polski sektor tytoniowy - Wesołowski, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The paper presents an analysis of 4 privatized companies of treasure of state in Poland, that in period from 1996 to 2007 showed significant height of value. The average value of sales in these companies has risen from 7 to 83 million euros. This has resulted in new technology solutions, hight-quality products as well as cigarette brands diversification. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 686-694